Capacity-building strategy for next-generation mental health research: embedding a national network infrastructure to grow mental health researcher capabilities and mental health lived-experience research leaders - Dana Jazayeri; Michelle Banfield; Caley Tapp; Caroline Tjung; Tegan Stettaford; Victoria Stewart; Giulietta Valuri; Terence W.H. Chong; Patricia Cullen; Martina McGrath; Rebecca Cooper; Amanda Wheeler; et al. (2025)
Internationally, capacity building for mental health implementation and translation research has lagged. A review of literature found initiatives since 2008 indicating limited dedicated attention to growing capabilities of early-to-mid-career mental health researchers, and little reporting of tailored career pathways and skills growth. Significant gaps in capacity building thus exist. This perspective article describes a networked infrastructure for a capacity building strategy of the Australian-based ALIVE National Centre for Mental Health Research Translation. The Centre was funded as a special initiative in mental health with an initial five-year investment. In 2022, the Centre established the first national, cross-disciplinary mental health Next Generation Researcher Network, including a tailored Lived-Experience Research Collective with the aim to grow future research leaders and establish career pathways embedded within the research activities of the Centre. After three years of operation, membership is upward of 280 people in the Next Generation Researcher Network and more than 250 people for the Collective. Specific components implemented as part of the strategy include a central coordination hub, coleadership approaches, coresearch models, tailored traineeships, skills-building through short courses and learning events, cocreation of resources, an online peer discussion platform and annual seed funding schemes. A continuous capacity-building strategy is critical for advancing global research agendas to improve mental health implementation and translation outcomes. Success requires network infrastructure to ensure research methodologies advance, and research addresses the priorities of people most impacted, and early and mid-career researcher capabilities across all research settings connected with universities and service sectors grow.